Words and their many meanings - Paradis, Carita (My University, 2014)
Words and their many meanings Professor Carita Paradis (University of Lund, Sweden) Words are very slippery customers. This is both good and bad for human communication – good if we want to be creative, flexible or vague and bad, if not. The purpose of this talk is to give a brief overview of how words mean in discourse and how language users can make sense of them. It points to the strong relation between meaning in language and our knowledge about the world, about the way we think in the world, who the speakers are, where they are and why are they talking.
Keywords: Sociolingüística